Morphophysiological responses and tolerance of various sweet corn (Zea mays convar. saccharata) hybrids to shade stress - VIRGIANA FITRI UTARI; MUHAMAD ACHMAD CHOZIN; DHIKA PRITA HAPSARI; ARYA WIDURA RITONGA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Utari VF, Chozin MA, Hapsari DP, Ritonga AW. 2023. Morphophysiological responses and tolerance of various sweet corn (Zea mays convar. saccharata) hybrids to shade stress. Biodiversitas 24: 4438-4447. Expanding lands for cultivating sweet corn (Zea mays convar. saccharata) is a strategy to increase its production. Yet, the available lands for sweet corn extensification might be those with existing tree stands with some extent of shading. Planting sweet corn under tree stands affects its growth and productivity since there is a reduction in light intensity, but some superior varieties might tolerate such stress. This study aimed to determine the growth, yield, and shade-tolerance levels of several sweet corn genotypes under shade stress. The experiment adopted a randomized complete block design consisting of two factors, namely shading (i.e. control or 0% shade and 50% shade) and sweet corn genotype (16 genotypes). The observed parameters included morphological traits (plant height, leaf number, leaf length, leaf width, and stem diameter), physiological traits (stomatal density and trichome density), yield attributes (cob weight with husks, cob weight without husks, cob length, cob diameter, and total soluble solid), and stress tolerance index (STI). The tested genotypes responded differently to shading. In general, 50% shade significantly reduced cob production, with an average decrease of more than 50% compared to the control. Commercial varieties, namely Exotic (G13), Talenta (G14), Paragon (G15), and Golden Boy (G16), had relatively higher STI values compared to the hybrids. Among the hybrids, the highest STI values were observed for genotypes resulting from the crosses SM7-8 × SM12-2 (G11) and SM11-6 × SM12-2 (G12). The results of this study recommend that commercial varieties can be cultivated under tree stands or low light intensity and can be used to develop high-yielding shade-tolerant sweet corn varieties.